Quantitation of the viral DNA present in cells transformed by UV-irradiated herpes simplex virus. - Davis, D B (1976)
Two cell lines biochemically transformed by UV-irradiated herpes simplex virus (HSV) each contain virus DNA. A comparison of the kinetics of reassociation of 3H-labeled HSV DNA in the presence and absence of either clone 139 (HSV-1 transformed) or clone 207 (HSV-2 transformed) DNA showed that the presence of transformed cell DNA increased the rate of reassociation of approximately 10% of the viral genome while having no effect on the remaining 90%. The Cot1/2 of this reaction was approximately 1,000 in each cell type, as compared to approximately 3,000 for the cellular unique sequences. These results suggest the presence of four to six copies of a 10% fragment of the virus DNA per cell. The DNA from a hamster fibroblast cell line morphologically transformed by UV-irradiated HSV-2 (333-8-9) did not affect the rate of reassociation of HSV-2 DNA, indicating that these cells had less than 3% of a viral genome present.